2021
DOI: 10.31219/osf.io/m84pe
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Youth Digital Skills Indicator: Report on the conceptualisation and development of the ySKILLS digital skills measure

Abstract: This report presents the youth Digital Skills Indicator (yDSI), a unique, extensively crossnationally validated measurement tool with 31 items, distributed over digital skills and digital knowledge questions, that can be used for large-scale population research. The yDSI is the only measurement tool for youth digital skills that has been tested using the full range of validation practices. Over a period of six months, consultation with experts (face validity), cognitive interviews (content validity), pilot sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…However, it is unclear what kinds of digital skills are most associated with technology-based learning activities (Livingstone et al, 2021). Taking into account the dimensions most frequently indicated in the frameworks on digital skills (Helsper et al, 2020) and preceding findings (Eynon & Malmberg, 2011;Metzger et al, 2013;Scherer et al, 2017;Tang & Chaw, 2016;Tirado-Morueta et al, 2017), the following hypotheses were formulated: H2. Students who have a high level of digital operational (H2a), communication (H2b), creative (H2c) and information (H2d) skills will frequently carry out technology-based learning activities.…”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is unclear what kinds of digital skills are most associated with technology-based learning activities (Livingstone et al, 2021). Taking into account the dimensions most frequently indicated in the frameworks on digital skills (Helsper et al, 2020) and preceding findings (Eynon & Malmberg, 2011;Metzger et al, 2013;Scherer et al, 2017;Tang & Chaw, 2016;Tirado-Morueta et al, 2017), the following hypotheses were formulated: H2. Students who have a high level of digital operational (H2a), communication (H2b), creative (H2c) and information (H2d) skills will frequently carry out technology-based learning activities.…”
Section: Hypothesesmentioning
confidence: 99%
“…However, to understand the digital empowerment of students, it is necessary to address how these skills relate to each other. Although there are conceptual models, such as the cyclical model proposed by Coiro and Hobbs (2017) or the model by Helsper et al (2020) from which the critical aspects of skills are emphasized, there are few empirical studies (2023) 18:10 that focus on the analysis of their relationships (e.g., Tirado-Morueta et al, 2017). In this context, the authors formulated the following hypotheses: H3.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants not only assess themselves too favourably but also claim to have traits they do not have or perform actions they do not perform (e.g. Helsper et al, 2020). For example, Hargittai (2009) showed that approximately 20% of participants claimed some understanding of made-up digital competence terms (i.e.…”
Section: The Aim Of the Studymentioning
confidence: 99%
“…This should be done in a closed digital environment that allows for results standardisation and does not favour particular operational systems, browsers, search engines or devices. This seemingly simple task is so difficult that even though we have elaborate testing frameworks today (Deursen & Van Dijk, 2010), actual operating tests that can measure online search skills in a valid and reliable way are still scarce (Haddon et al, 2020;Hargittai & Hsieh, 2012;Helsper et al, 2020;ITU, 2020).…”
mentioning
confidence: 99%